RELATIONSHIP OF PHYSICAL FITNESS AND PHYSICAL ACTIVITY IN BEGINNERS LEVEL BASKETBALL PLAYERS DURING COVID-19 - Arnaz Anggoro Saputro (International Journal of Basketball Studies, 2022)
This study aims to determine the correlation between physical activity and physical fitness for beginner-level basketball players at Ploso High School in the 2021-2022 academic year. The method used in this study is a survey method with a correlational study. The sampling technique used total sampling, so the entire population of 20 people was used as the subject of this research. Instruments to measure physical activity use the Physical Activity Questionnaire for Older Children (PAQC) and to measure physical fitness use TKJI. Data analysis using SPSS version 25 with a simple correlational test. The results of data analysis show that the correlation between physical activity and physical fitness is r = 0.78, so it can be concluded that there is a positive correlation between physical activity and physical fitness for beginner level basketball athletes at Ploso High School in the 2021-2022 academic year.